The Mechanism of Electronic Trials in Criminal and Civil Cases (A Study at the Takengon Class 1B Sharia Court) - Rian Afriandi Putra; Mhd. Azhali Siregar; T. Riza Zarzani (PT. Sinergi Legal Publisher, 2025)
Digital transformation in the Indonesian judicial system has become a strategic necessity in facing the challenges of the times and emergency conditions such as the COVID-19 pandemic. The Takengon Sharia Court Class IB, as a judicial institution in the special autonomy region of Aceh, has also implemented an electronic trial system (e-Court and e-Litigation) in civil cases and some Islamic criminal cases (jinayat). This study aims to analyze the case resolution mechanism, the implementation of the electronic trial system, and the obstacles faced in practice. Using the normative-empirical legal research method, the study was conducted through regulatory analysis such as PERMA Number 3 of 2018, PERMA Number 8 of 2022, and Aceh Qanun Number 6 and 7 of 2013–2014, supplemented by interviews and field observations. The results of the study show that the e-Court system has provided efficiency in civil cases, especially in terms of registration, payment, summons, and exchange of litigation documents. However, the implementation of online trials in jinayat cases is still limited due to the characteristics of Islamic criminal procedural law which requires the physical presence of the parties in the courtroom. Substantive obstacles include disharmony between national procedural law and PERMA, as well as limited mediation mechanisms and public openness. Meanwhile, technical obstacles include low digital literacy among the community, uneven infrastructure, and readiness of human resources. Therefore, harmonization of regulations, improvement of technological facilities, and ongoing training are needed so that the electronic justice system can function optimally and guarantee access to justice substantively.